A study on awareness about eye health care and eye donation among secondary level students of North Kolkata, India - Biswas, J; Bandyopadhyay, S; Das, D; Mondal, K K; Saha, I; Ray, B (Kathmandu University Medical Journal, 2012)
Background Corneal blindness is one of the important types of blindness that can be prevented by proper health care education and conventionally cured by corneal transplantation for which awareness regarding eye donation is essential. Objectives The aim of the study is to assess the awareness of eye health care and eye donation among secondary level school students of North Kolkata. Methods It was a cross-sectional study. Settings: Eight Government aided schools of North Kolkata, West Bengal, India. A total of 1525 students of standard VIII, IX and X of Government aided schools of North Kolkata participated in this study. A pre-tested, semi-structured questionnaire was administered on eye health care and eye donation. Results 1284 (84.2%) participants opined that awareness on eye health care can prevent most of the blindness and 1206 (79.1%) students knew that Vitamin A has important role in prevention of childhood blindness. Majority, 1235 (81.0%) students were aware of eye donation after death while only 489 (32.1%) participants knew that the ideal time for eye donation is within 6 hours of death. 802 (52.6%) participants mentioned printed and electronic media (like newspaper and television) as the major source of information on eye donation. Conclusions Media publicity to increase awareness of eye donation and eye health care is not enough. Strategies have to be developed to educate the students, so that they can act as motivators for enhancing eye donation and increasing eye health care awareness in the community. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6219 Kathmandu Univ Med J 2010;8(3):317-20